Dynamic Formation of Hybrid Peptidic Capsules by Chiral Self‐Sorting and Self‐Assembly1. (8th October 2014) - Jędrzejewska, Hanna; Wierzbicki, Michał; Cmoch, Piotr; Rissanen, Kari; Szumna, Agnieszka
Abstract Owing to their versatility and biocompatibility, peptide‐based self‐assembled structures constitute valuable targets for complex functional designs. It is now shown that artificial capsules based on β‐barrel binding motifs can be obtained by means of dynamic covalent chemistry (DCC) and self‐assembly. Short peptides (up to tetrapeptides) are reversibly attached to resorcinarene scaffolds. Peptidic capsules are thus selectively formed in either a heterochiral or a homochiral way by simultaneous and spontaneous processes, involving chiral sorting, tautomerization, diastereoselective induction of inherent chirality, and chiral self‐assembly. Self‐assembly is shown to direct the regioselectivity of reversible chemical reactions. It is also responsible for shifting the tautomeric equilibrium for one of the homochiral capsules. Two different tautomers (keto‐enamine hemisphere and enol‐imine hemisphere) are observed in this capsule, allowing the structure to adapt for self‐assembly.